A Systematic Approach to Review of in vitro Methods in Brain Tumour Research (SAToRI-BTR): Development of a Preliminary Checklist for Evaluating Quality and Human Relevance - Bracher, Mike; Pilkington, Geoffrey J.; Hanemann, C. Oliver; Pilkington, Karen (Frontiers in Bioengineering and Biotechnology, 2020)
Background - A wide range of human in vitro methods have been developed and there is considerable interest in the potential of these studies to address questions related to clinical (human) use of drugs, and the pathobiology of tumours. This requires agreement on how to assess the strength of evidence available (i.e. quality and quantity) and the human-relevance of such studies. The SAToRI-BTR (Systematic Approach To Review of In vitro methods in Brain Tumour Research) project seeks to identify relevant appraisal criteria to aid planning and/or evaluation of brain tumour studies using in vitro methods. Objectives – To identify criteria for evaluation of quality and human relevance of in vitro brain tumour studies; to assess the general acceptability of such criteria to senior scientists working within the field. Methods – Stage one involved identification of potential criteria for evaluation of in vitro studies through: (1) an international survey of brain tumour researchers; (2) interviews with scientists, clinicians, regulators, and journal editors; (3) analysis of relevant reports, documents, and published studies. Through content analysis of findings, an initial list of criteria for quality appraisal of in vitro studies of brain tumours was developed. Stage two involved review of the criteria by an expert panel (Delphi process). Results – Results of stage one indicated that methods for and quality of review of in vitro studies are highly variable, and that improved reporting standards are needed. 129 preliminary criteria were identified; duplicate and highly context-specific items were removed, resulting in 48 criteria for review by the expert (Delphi) panel. 37 criteria reached agreement, resulting in a provisional checklist for appraisal of in vitro studies in brain tumour research. Conclusion – Through a systematic process of collating assessment criteria and subjecting these to expert review, SAToRI-BTR has resulted in preliminary guidance for appraisal of in vitro brain tumour studies. Further development of this guidance, including investigating strategies for adaptation and dissemination across different sub-fields of brain tumour research, as well as the wider in vitro field, is planned.